Stacs 2007
DOI: 10.1007/978-3-540-70918-3_37
|View full text |Cite
|
Sign up to set email alerts
|

On Symmetric Signatures in Holographic Algorithms

Abstract: The most intriguing aspect of the new theory of matchgate computations and holographic algorithms by Valiant [12] [14] is that its reach and ultimate capability are wide open. The methodology produces unexpected polynomial time algorithms solving problems which seem to require exponential time. To sustain our belief in P = NP, we must begin to develop a theory which captures the limit of expressibility and power of this new methodology.In holographic algorithms, symmetric signatures have been particularly use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…In almost all cases [29,3], the successful design of a holographic algorithm was accomplished by a basis of size 1. In [30], initially Valiant used a basis of size 2 to show # 7 Pl-Rtw-Mon-3CNF ∈ P. Then it was pointed out in [6] that even in that case the same can be done with a basis of size 1. In [8] and [9], we show that this is generally true, i.e., higher dimensional bases do not extend the reach of holographic algorithms.…”
Section: The Basis Manifold Mmentioning
confidence: 96%
See 1 more Smart Citation
“…In almost all cases [29,3], the successful design of a holographic algorithm was accomplished by a basis of size 1. In [30], initially Valiant used a basis of size 2 to show # 7 Pl-Rtw-Mon-3CNF ∈ P. Then it was pointed out in [6] that even in that case the same can be done with a basis of size 1. In [8] and [9], we show that this is generally true, i.e., higher dimensional bases do not extend the reach of holographic algorithms.…”
Section: The Basis Manifold Mmentioning
confidence: 96%
“…In [6], we gave a complete characterization of all the realizable symmetric signatures (Theorems 2.3-2.5). These tell us exactly what signatures can be realized over some bases.…”
Section: Simultaneous Realizability Of Symmetric Signaturesmentioning
confidence: 98%
“…Such algorithms have been studied in depth and further developed by Cai et al [1][2][3][4][5][6][7][8].…”
Section: Historymentioning
confidence: 99%
“…In [4], we showed that a generator for [1, 0, 1] and a recognizer for [0, 1, 1, 1] over Z 7 can also be simultaneously realized on the following basis of size 1: [( 1 6 ) , ( 3 5 )]. The natural question is whether this is luck or this is universally true.…”
Section: An Outline Of Our Basis Collapse Theoremmentioning
confidence: 99%
“…There is another basis of size 1, for which one can devise a holographic algorithm which also solves # 7 Pl-Rtw-Mon-3CNF in polynomial time. The main result in [4] is a characterization of all the realizable symmetric signatures over all bases of size 1. The holographic algorithm for # 7 Pl-Rtw-Mon-3CNF using a basis of size 1 follows as a consequence.…”
Section: Introductionmentioning
confidence: 99%